Analysis Competitiveness Improvement Strategy Product Rice of Perum Bulog Cabang Makassar. - Amalia Nur, Mufridha; Darwis, Muhammad; Rivai, Andi Muhammad; Niswaty, Risma (Pinisi Business Administration Review, 2025)
Analysis of Strategies for Increasing the Competitiveness of Rice Products at the Perum Bulog Cabang Makassar.. Thesis. Business Administration Study Program. Faculty of Social Sciences and Law. Makassar public university. (Supervised by Muhammad Darwis and Andi Muhammad Rivai). This study aims to determine and analyze strategies to increase the competitiveness of rice products at the BulogBranch of Perum Makassar. To achieve this goal, this study used a qualitative approach, this study took five respondents, consisting of A.M Retail, Direct and E-Commerce, A.M Distributor, Commercial Staff, and consumers. Data collection procedures used were in-depth interviews and documentation. The interview technique was carried out in a structured manner using interview guidelines. The results of this study indicate that the Makassar Branch of Bulog Perum has implemented a good and effective strategy to increase competitiveness in accordance with Michael E. Porter's theory. In carrying out the implementation of the competitiveness improvement strategy, Perum Bulog Makassar Branch conducts research on low-cost strategies, product differentiation strategies, innovation strategies, growth strategies, and cooperation strategies to determine a competitiveness strategy.Keywords: Strategy for Increasing Competitiveness, Rice, Perum Bulog